A core-shell nanowire FeOOH@CoMnP composite material and its preparation method and application
By preparing core-shell nanowire-shaped FeOOH@CoMnP composite materials on a foam nickel matrix, the problem of low oxygen evolution reaction rate in electrolytic water hydrogen production technology is solved, and efficient electrocatalytic performance and long-term stability are achieved. It is suitable for electrolysis. Hydrogen and metal air batteries.
Patent Information
- Application Number
- CN202311740601.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-12-18
AI Technical Summary
In the existing electrolytic hydrogen production technology, the oxygen evolution reaction (OER) rate occurs in the anode, the cost of precious metal catalysts is high and the reserves are limited, and the catalytic efficiency and stability of a single structural catalyst cannot meet the needs of industrial production.
Core-shell nanowire FeOOH@CoMnP composite material is used as a catalyst to prepare through hydrothermal synthesis and calcination phosphating reactions, using foam nickel matrix, ammonium fluoride and urea to promote cobalt-manganese layer nucleation, and combined with chemical bath method to deposit FeOOH. Form a graded nanoarray structure to increase the specific surface area and electroactive sites of the catalyst.
It significantly reduces the overpotential of the oxygen evolution reaction, improves the electrocatalytic performance and long-term stability, and is suitable for electrolyzing hydrogen production and metal air batteries, with excellent electrochemical performance and broad application prospects.
Smart Images

Figure CN117772244B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel functional nanomaterials, and specifically relates to a core-shell nanowire FeOOH@CoMnP composite material and a preparation method and application thereof. Background Art
[0002] The depletion crisis of fossil energy and the intensification of environmental pollution have prompted scientific researchers to vigorously develop renewable clean energy to alleviate the energy crisis and improve environmental problems. In the emerging renewable clean energy industry, water electrolysis to produce hydrogen is considered a promising technology. However, the efficiency of water electrolysis to produce hydrogen is greatly limited by the rate of oxygen evolution reaction (OER) occurring at the anode. According to research reports, precious metals such as iridium oxide (IrO2) and ruthenium oxide (RuO2) are the most efficient catalysts, but the high cost and limited reserves make them impossible to promote on a large scale. Transition metals are ideal alternative catalysts due to their unique electronic structure and diversity of adsorption sites. At present, the catalytic efficiency and long-term stability of most single-structure catalysts cannot meet the needs of industrial production applications, and research hotspots are also mainly focused on multiple structural composites to improve catalytic efficiency and increase stability. Summary of the invention
[0003] In view of the shortcomings of the existing methods, the present invention provides a core-shell nanowire FeOOH@CoMnP composite material and a preparation method and application thereof.
[0004] To achieve the above object, the present invention adopts the following technical solution:
[0005] A method for preparing a core-shell nanowire FeOOH@CoMnP composite material comprises the following steps:
[0006] Step 1: Add the cobalt source, manganese source, additives and active additives into deionized water in sequence, and stir evenly to form a precursor solution;
[0007] Step 2: The precursor solution obtained in step 1 is transferred into a reaction tank, and nickel foam is added at the same time, which is sealed and then placed in a muffle furnace for hydrothermal synthesis reaction. After the reaction is completed, the reaction is cooled with the furnace, and then the nickel foam after the reaction is washed and dried;
[0008] Step 3: Under the protection of an inert atmosphere, the nickel foam loaded with cobalt-manganese compounds and the sodium hypophosphite obtained in step 2 are placed at the downwind and upwind ports of a tubular furnace, respectively, to perform a calcination phosphating reaction;
[0009] Step 4: Immerse the product obtained in step 3 into a room temperature FeCl3 solution using a chemical bath method, and drop H2O2 solution, wash and dry after sufficient reaction to obtain the target product.
[0010] Preferably, the cobalt source in step 1 is one or more of cobalt oxalate, cobalt chloride, cobalt nitrate and cobalt sulfate, and the molar concentration of the cobalt source in the precursor solution is 0.01-0.1 mol / L.
[0011] Preferably, the manganese source in step 1 is one or more of manganese oxalate, manganese chloride, manganese nitrate and manganese sulfate, and the molar concentration of the manganese source in the precursor solution is 0.001-0.05 mol / L.
[0012] Preferably, in step 1, the additive is ammonium fluoride, and the concentration of ammonium chloride in the precursor solution is 0.01-0.5 mol / L; the active agent is urea, and the concentration of urea in the precursor solution is 0.05-0.5 mol / L.
[0013] Preferably, the nickel foam in step 2 is pretreated before being added, and the pretreatment is ultrasonic cleaning using hydrochloric acid, anhydrous ethanol and deionized water in sequence, followed by drying.
[0014] Preferably, the hydrothermal synthesis reaction in step 2 is heated to 100-160° C. at a heating rate of 5-15° C. / min and kept warm for 1-12 hours.
[0015] Preferably, the mass ratio of the sodium hypophosphite in step 3 to the nickel foam in step 2 is 2-5:1, and the calcination phosphating reaction is heated to 300-400°C at a heating rate of 1-5°C / min, and the calcination time is 1-3h.
[0016] Preferably, the concentration of the FeCl3 solution in step 4 is 0.05-0.1 mol / L, the dosage ratio of the FeCl3 solution to the nickel foam in step 2 is 20-30 mL:0.1 g, the dosage ratio of the H2O2 solution to the nickel foam in step 2 is 5-10 mL:0.1 g, and the reaction time is 0.5-5 min.
[0017] A core-shell nanowire FeOOH@CoMnP composite material prepared by the above preparation method.
[0018] The invention discloses an application of the core-shell nanowire FeOOH@CoMnP composite material prepared by the above preparation method as a catalyst for oxygen evolution reaction in water electrolysis.
[0019] The positive beneficial effects of the present invention are:
[0020] 1. The present invention uses nickel foam as a substrate. The three-dimensional network structure of nickel foam has a large specific surface area and a smooth and flat surface of the grains, which is conducive to the uniform nucleation and growth of cobalt and manganese ions on its surface. The present invention directly prepares the catalytic material on the nickel foam substrate, avoids the use of a binder and a conductive agent, has a simple process and low cost.
[0021] 2. In the hydrothermal synthesis process, ammonium fluoride and urea are added to promote the reaction and nano-size control, promote the nucleation of cobalt-manganese layered double hydroxide, and ammonium fluoride reacts with water to gradually generate OH - , the cobalt and manganese ions can be controlled to stably and uniformly nucleate on the surface of nickel foam. Compared with the traditional direct addition of precipitants such as NaOH and KOH, the cobalt and manganese ions can quickly nucleate and grow in a short time, which solves the technical problem of "it is difficult to control the nucleation of cobalt and manganese ions stably on the surface of nickel foam, resulting in uncontrollable morphology and structure". The prepared cobalt-manganese compound has uniform particle size and consistent morphology and structure.
[0022] 3. The present invention obtains a cobalt manganese phosphide CoMnP composite material by calcining phosphating reaction, and then adopts a chemical bath method. Hydrogen peroxide has a strong oxidizing effect, which helps to quickly deposit FeOOH on the surface of cobalt manganese phosphide CoMnP in a very short reaction time. FeOOH has excellent catalytic performance for oxygen evolution reaction and is embedded in CoMnP nanowires to form a hierarchical nanoarray structure directly grown on a nickel foam conductive substrate, which can increase the specific surface area of the catalyst, mitigate the volume change ability, and dope heterogeneous atoms to provide more electroactive sites and regulate the electronic structure; the FeOOH thin layer has a thickness of 0.5 to 5 nm. Due to the excellent conductivity of the CoMnP carrier and the small size effect of the FeOOH thin layer, it has more abundant and sufficient active sites, which is conducive to electron transmission, and the Fe 3+ Ions and Co 2+ Ion, Mn 2+ The ions formed a synergistic catalytic enhancement effect. The obtained electrocatalyst FeOOH@CoMnP was applied to the test environment of 1 mol / L KOH solution, and the overpotential of the oxygen evolution reaction was significantly reduced to 10 mA cm -2 The overpotential is only 220 mV at a current density of 1.38 Å, and the Tafel slope is 65.21 mV·dec -1 , with excellent electrochemical properties. At the same time, the ultrafine FeOOH nanoparticles are fixed on the CoMnP nanowire carrier to prevent them from agglomerating and decaying, making FeOOH@CoMnP stable for more than 40 hours. It can be used as a catalyst material for water electrolysis to produce hydrogen and oxygen and metal-air batteries, and has broad application prospects in the fields of energy conversion and storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The actual picture of the FeOOH@CoMnP composite material and nickel foam prepared in Example 1; wherein: a is the nickel foam pretreated in step 2 of Example 1, and b is the FeOOH@CoMnP composite material prepared in Example 1;
[0024] Figure 2 This is a scanning electron microscope image of the CoMnP material prepared in Comparative Example 1;
[0025] Figure 3 The scanning electron microscope image of the FeOOH material prepared in Comparative Example 2;
[0026] Figure 4 This is a scanning electron microscope image of the FeOOH@CoMnP composite material prepared in Example 1;
[0027] Figure 5 This is a transmission electron microscopy image of the FeOOH@CoMnP composite material prepared in Example 1;
[0028] Figure 6 is the X-ray diffraction pattern of the FeOOH@CoMnP composite material prepared in Example 1;
[0029] Figure 7 LSV curves of the oxygen evolution reaction of the FeOOH@CoMnP composite material prepared in Example 1, the CoMnP of Comparative Example 1, and the FeOOH material of Comparative Example 2 in an alkaline environment;
[0030] Figure 8 It is a Tafel slope curve of the oxygen evolution reaction of the FeOOH@CoMnP composite material prepared in Example 1, the CoMnP of Comparative Example 1, and the FeOOH material of Comparative Example 2 in an alkaline environment;
[0031] Fig. 9 The FeOOH@CoMnP composite material prepared in Example 1 was subjected to an alkaline environment at 10 mA·cm- 2 IT stability test curve in oxygen evolution reaction under current density;
[0032] Fig.10 The FeOOH@CoMnP composite material prepared in Example 1 is 10-100 mA·cm- 2 Step IT stability test curve in oxygen evolution reaction under current density;
[0033] Fig.11 The double layer capacitance C of the FeOOH@CoMnP composite material prepared in Example 1, the CoMnP of Comparative Example 1, and the FeOOH material of Comparative Example 2 under alkaline environment for oxygen evolution reaction dl Graphs;
[0034] Fig.12 EIS curves of the FeOOH@CoMnP composite material prepared in Example 1, the CoMnP of Comparative Example 1, and the FeOOH material of Comparative Example 2 in an alkaline environment;
[0035] Fig.13The FeOOH@CoMnP composite material prepared in Example 2 was enlarged to 1×10 4 Scanning electron microscope image at multiple magnifications;
[0036] Fig.14 The FeOOH@CoMnP composite material prepared in Example 2 was enlarged to 1×10 5 Scanning electron microscope image at multiple magnifications. DETAILED DESCRIPTION
[0037] In order to better understand the content of the present invention, the present invention is further described in detail below in conjunction with embodiments and drawings, but the implementation mode and protection scope of the present invention are not limited thereto.
[0038] Example 1
[0039] A method for preparing a core-shell nanowire FeOOH@CoMnP composite material comprises the following steps:
[0040] (1) 0.3850 g of cobalt nitrate hexahydrate, 0.0212 g of manganese sulfate monohydrate, 0.8882 g of ammonium fluoride, and 0.22 g of urea were dissolved in 50 mL of deionized water, with molar concentrations of 0.026 mol / L, 0.0025 mol / L, 0.48 mol / L, and 0.073 mol / L, respectively. The mixture was stirred for 20 min at a stirring speed of 200 r / min, and then uniformly stirred to obtain a precursor solution.
[0041] (2) Take a nickel foam with a size of 1 cm × 4 cm × 0.16 cm and a density of 0.42 g cm -3 , respectively, using 1 mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 min, and drying at room temperature for 12 h to remove oil and oxides on the surface of the nickel foam to obtain a pretreated nickel foam weighing 0.1 g, placing the treated nickel foam into the precursor solution of step (1), and transferring it to a 100 mL polytetrafluoroethylene tank, and configuring a PVA outer tank, sealing and tightening it, heating it to 120°C in a muffle furnace at a heating rate of 10°C / min, keeping it warm for 6 h, cooling it with the furnace after the reaction is completed, and then washing the reacted nickel foam with deionized water for 3 times, and drying it at room temperature for 12 h;
[0042] (3) Under an inert atmosphere, the nickel foam loaded with cobalt-manganese compound obtained in step (2) and 0.5 g of sodium hypophosphite are placed at the downwind and upwind ports of a tube furnace, respectively, and heated to 350° C. at a heating rate of 5° C. / min for calcination for 3 h;
[0043] (4) The product obtained in step (3) was immersed in a 0.1 mol / L FeCl3 solution with a volume of 20 mL by a chemical bath method, and 5 mL of H2O2 solution was added dropwise. After reacting for 0.5 min, it was washed with deionized water three times and dried at room temperature for 12 h to obtain the target product.
[0044] Comparative Example 1
[0045] A method for preparing a CoMnP composite material comprises the following steps:
[0046] (1) 0.3850 g of cobalt nitrate hexahydrate, 0.0212 g of manganese sulfate monohydrate, 0.8882 g of ammonium fluoride, and 0.22 g of urea were dissolved in 50 mL of deionized water, with molar concentrations of 0.026 mol / L, 0.0025 mol / L, 0.48 mol / L, and 0.073 mol / L, respectively. The mixture was stirred for 20 min at a stirring speed of 200 r / min, and then uniformly stirred to obtain a precursor solution.
[0047] (2) Take a nickel foam with a size of 1 cm × 4 cm × 0.16 cm and a density of 0.42 g cm -3 , respectively, using 1 mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 min, and drying at room temperature for 12 h to remove oil and oxides on the surface of the nickel foam to obtain a pretreated nickel foam weighing 0.1 g, placing the treated nickel foam into the precursor solution of step (1), and transferring it to a 100 mL polytetrafluoroethylene tank, and configuring a PVA outer tank, sealing and tightening it, heating it to 120°C in a muffle furnace at a heating rate of 10°C / min, keeping it warm for 6 h, cooling it with the furnace after the reaction is completed, and then washing the reacted nickel foam with deionized water for 3 times, and drying it at room temperature for 12 h;
[0048] (3) Under an inert atmosphere, the nickel foam loaded with nanomaterials obtained in step (2) and 0.5 g of sodium hypophosphite are placed at the downwind and upwind ports of a tube furnace, respectively, and heated to 350° C. at a heating rate of 5° C. / min. The calcination time is 3 h, thereby obtaining the target product CoMnP.
[0049] Comparative Example 2
[0050] A method for preparing an iron oxyhydroxide (FeOOH) material comprises the following steps:
[0051] (1) Take a nickel foam with a size of 1 cm × 4 cm × 0.16 cm and a density of 0.42 g cm -3, using 1 mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 min respectively, and drying at room temperature for 12 h to remove oil and oxides on the surface of the nickel foam, to obtain a pretreated nickel foam with a weight of 0.1 g;
[0052] (2) The pretreated nickel foam was immersed in a 0.1 mol / L FeCl3 solution with a volume of 20 mL, and 5 mL of H2O2 solution was added dropwise. After fully reacting for 0.5 min, it was washed with deionized water for 3 times and dried at room temperature for 12 h to obtain iron oxide hydroxide (FeOOH) product.
[0053] Figure 1 The nickel foam after pretreatment and the FeOOH@CoMnP of Example 1 are shown in FIG. Figure 1 It can be seen that the nickel foam after pretreatment in Figure a is medium gray with obvious foam pores, while the nickel foam after reaction in Figure b has reaction products deposited on the surface and the color has turned to black-brown with no other changes.
[0054] Depend on Figure 2 It can be seen that the CoMnP obtained in Comparative Example 1 has uniform particle size, nanowire-like morphology, smooth surface and consistent structure.
[0055] Depend on Figure 3 It can be seen that the FeOOH obtained in Comparative Example 2 is amorphous and connected into one piece.
[0056] Depend on Figure 4 It can be seen that the FeOOH@CoMnP composite material obtained in Example 1 is a nanowire covered with a coating, and the surface of the nanowire is rough.
[0057] from Figure 5 From the transmission electron microscope image of the FeOOH@CoMnP composite material obtained in Example 1, it can be seen that the sample is in the shape of nanowires, the inner core nanowire particle size is about 50nm, and a coating is attached to the outside, and the coating thickness is about 15-20nm.
[0058] Figure 6 This is the XRD image of the FeOOH@CoMnP composite material prepared in Example 1. The FeOOH@CoMnP composite material shows obvious main diffraction peaks corresponding to CoP and MnP, but the 2θ angles corresponding to different crystal planes of FeOOH are not obviously detected, indicating that it is amorphous and non-crystalline.
[0059] Depend on Figure 7 It can be seen that in 1 mol / L KOH solution, without IR compensation, it is obvious that the oxygen evolution overpotential of FeOOH@CoMnP is significantly lower than that of the comparative examples FeOOH and CoMnP. -2When the current is , the required oxygen evolution overpotential is only 220 mV, which is significantly lower than that of CoMnP and FeOOH in the comparative example, indicating that the FeOOH@CoMnP composite material has good catalytic ability for oxygen evolution reaction.
[0060] Depend on Figure 8 It can be seen that the Tafel slope of FeOOH@CoMnP prepared in Example 1 is 65.21 mV·dec -1 , which is significantly smaller than 86.03 mV·dec of FeOOH -1 and 126.59mV·dec of CoMnP -1 , indicating that the FeOOH@CoMnP composite material of the present invention has a faster electron migration rate and good catalytic ability for oxygen evolution reaction.
[0061] Depend on Fig. 9 It can be seen that the long-term stability of the FeOOH@CoMnP composite material obtained in Example 1 is -2 When the oxygen evolution reaction potential is stabilized at 1.45 V, the stable time is more than 40 hours.
[0062] Depend on Fig.10 It can be seen that the step time stability of the FeOOH@CoMnP composite material obtained in Example 1 is -2 When the oxygen evolution overpotential of the sample can remain stable at each stage, there is no performance degradation, which proves that the FeOOH@CoMnP composite material has excellent electrical stability.
[0063] Depend on Fig.11 It can be seen that the C prepared in Example 1 dl Layered double layer capacitance: The layered double layer capacitance of FeOOH@CoMnP is 18.57 mF·cm -2 , which is significantly higher than the 9.07 mF·cm of FeOOH in the comparative example. -2 and 6.51 mF·cm of CoMnP -2 , indicating that the FeOOH@CoMnP composite material has a larger electrochemical active area.
[0064] Depend on Fig.12 From the EIS curve, it can be seen that the charge transfer impedance of FeOOH@CoMnP is significantly reduced, indicating that the FeOOH@CoMnP composite material has faster electron conduction ability.
[0065] Example 2
[0066] A method for preparing a core-shell nanowire FeOOH@CoMnP composite material comprises the following steps:
[0067] (1) 0.4657 g of cobalt nitrate hexahydrate, 0.0676 g of manganese sulfate monohydrate, 0.0703 g of ammonium fluoride, and 0.6006 g of urea were dissolved in 50 mL of deionized water, with molar concentrations of 0.032 mol / L, 0.0080 mol / L, 0.038 mol / L, and 0.2 mol / L, respectively, and magnetically stirred for 20 min at a stirring speed of 200 r / min to obtain a precursor solution;
[0068] (2) Take a nickel foam with a size of 1 cm × 4 cm × 0.16 cm and a density of 0.42 g cm -3 , respectively, using 1 mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 min, and drying at room temperature for 12 h to remove oil and oxides on the surface of the nickel foam to obtain a pretreated nickel foam with a weight of 0.12 g, placing the treated nickel foam into the precursor solution of step (1), and transferring it to a 100 mL polytetrafluoroethylene tank, and configuring a PVA outer tank, sealing and tightening it, heating it to 120°C in a muffle furnace at a heating rate of 10°C / min, keeping it warm for 3 h, cooling it with the furnace after the reaction is completed, and then washing the reacted nickel foam with deionized water for 3 times, and drying it at room temperature for 12 h;
[0069] (3) Under an inert N2 atmosphere, the nickel foam loaded with nanomaterials obtained in step (2) and 0.3 g of sodium hypophosphite are placed at the downwind and upwind ports of a tubular furnace, respectively, and heated to 400°C at a heating rate of 5°C / min, and the calcination time is 3 h.
[0070] (4) The product obtained in step (3) was immersed in a 0.1 mol / L FeCl3 solution with a volume of 30 mL by a chemical bath method, and 10 mL of H2O2 solution was added dropwise. After fully reacting for 2 min, it was washed with deionized water 3 times and dried at room temperature for 12 h to obtain the target product.
[0071] Fig.13 and 14 This is the SEM image of FeOOH@CoMnP prepared in Example 2. It can be seen from the two figures that the obtained FeOOH@CoMnP composite material is a nanowire morphology structure, and forms a multi-bundle cross-linked nanocone morphology. The surface of the nanocone is rough and has a scaly coating, which contains more catalytic active sites, which is beneficial to improving the electrocatalytic efficiency of the sample.
[0072] Example 3
[0073] A core-shell nanowire FeOOH@CoMnP composite material prepared by the preparation method of embodiment 1 or 2 above.
[0074] An application of a core-shell nanowire FeOOH@CoMnP composite material prepared by the preparation method of the above embodiment 1 or 2 as a catalyst for oxygen evolution reaction in electrolysis of water.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a core-shell nanowire FeOOH@CoMnP composite material. It is characterized in that The following steps are involved: Step 1: Add the cobalt source, manganese source, additives and active additives into deionized water in sequence, and stir evenly to form a precursor solution; Step 2: The precursor solution obtained in step 1 is transferred into a reaction tank, and nickel foam is added at the same time, which is sealed and then placed in a muffle furnace for hydrothermal synthesis reaction. After the reaction is completed, the reaction is cooled with the furnace, and then the nickel foam after the reaction is washed and dried; Step 3: Under the protection of an inert atmosphere, the nickel foam loaded with cobalt-manganese compounds and sodium hypophosphite obtained in step 2 are placed at the downwind and upwind ports of a tubular furnace, respectively, to perform a calcination phosphating reaction; Step 4: The product obtained in step 3 is immersed in a room temperature FeCl 3 The solution was added with H 2 O 2 The solution is washed and dried after sufficient reaction to obtain the target product; FeCl 3 The concentration of the solution is 0.05-0.1 mol / L, and the FeCl 3 The amount ratio of the solution to the nickel foam in step 2 is 20-30 mL: 0.1 g, and the H 2 O 2 The dosage ratio of the solution to the nickel foam described in step 2 is 5-10 mL: 0.1 g, and the reaction time is 0.5-5 min.
2. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: The cobalt source in step 1 is one or more of cobalt oxalate, cobalt chloride, cobalt nitrate and cobalt sulfate, and the molar concentration of the cobalt source in the precursor solution is 0.01-0.1 mol / L.
3. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: In step 1, the manganese source is one or more of manganese oxalate, manganese chloride, manganese nitrate and manganese sulfate, and the molar concentration of the manganese source in the precursor solution is 0.001-0.05 mol / L.
4. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: In step 1, the additive is ammonium fluoride, and the concentration of ammonium fluoride in the precursor solution is 0.01-0.5 mol / L; the active auxiliary agent is urea, and the concentration of urea in the precursor solution is 0.05-0.5 mol / L.
5. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: The nickel foam in step 2 is pretreated before being added, and the pretreatment is ultrasonic cleaning using hydrochloric acid, anhydrous ethanol and deionized water in sequence, and then drying.
6. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: The hydrothermal synthesis reaction in step 2 is heated to 100-160° C. at a heating rate of 5-15° C. / min and kept warm for 1-12 hours.
7. The method for preparing the core-shell nanowire FeOOH@CoMnP composite material according to claim 1, Features: The mass ratio of the sodium hypophosphite in step 3 to the nickel foam in step 2 is 2-5:1, and the calcination phosphating reaction is heated to 300-400°C at a heating rate of 1-5°C / min, and the calcination time is 1-3h.
8. A core-shell nanowire FeOOH@CoMnP composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the core-shell nanowire FeOOH@CoMnP composite material prepared by the preparation method according to any one of claims 1 to 7 as a catalyst for oxygen evolution reaction in water electrolysis.
Citation Information
Patent Citations
Preparation method of Mn-doped CoP nanowire modified nanosheet array layered structure supercapacitor electrode material
CN108511202A
